2002
DOI: 10.1037/0022-006x.70.4.1022
|View full text |Cite
|
Sign up to set email alerts
|

Does imaginal exposure exacerbate PTSD symptoms?

Abstract: Symptom exacerbation (i.e., treatment side effects) has often been neglected in the psychotherapy literature. Although prolonged exposure has gained empirical support for the treatment of chronic posttraumatic stress disorder (PTSD), some have expressed concem that imaginal exposure, a component of this therapy, may cause symptom exacerbation, leading to inferior outcome or dropout. In the present study, symptom exacerbation was examined in 76 women with chronic PTSD. To define a "reliable" exacerbation, we us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

23
244
5
7

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 312 publications
(279 citation statements)
references
References 31 publications
23
244
5
7
Order By: Relevance
“…According to the final multilevel model, it appears that patients in both treatments experience rapid initial declines in self-reported PTSD symptoms, which then level off over time. It should be noted that prior studies have shown that approximately 10 percent of patients may experience an exacerbation following the first imaginal exposure in PE, when patients are asked to describe in detail what happened during their traumatic events (Foa, Zoellner, Feeny, Hembree, & Alvarez-Conrad, 2007). This exacerbation in symptoms was not observed in the present study.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…According to the final multilevel model, it appears that patients in both treatments experience rapid initial declines in self-reported PTSD symptoms, which then level off over time. It should be noted that prior studies have shown that approximately 10 percent of patients may experience an exacerbation following the first imaginal exposure in PE, when patients are asked to describe in detail what happened during their traumatic events (Foa, Zoellner, Feeny, Hembree, & Alvarez-Conrad, 2007). This exacerbation in symptoms was not observed in the present study.…”
Section: Discussioncontrasting
confidence: 69%
“…Patients who have ignored or avoided their PTSD symptoms as a form a symptom management may experience an initial increase in PTSD symptoms, especially when they first begin confronting trauma reminders. Encouragingly, Foa et al (2007) found that patients who experienced an exacerbation in their PTSD symptoms experienced similar benefits from PE when compared to patients who did not report an exacerbation in symptoms. Their findings have not been confirmed for CPT patients.…”
Section: Discussionmentioning
confidence: 95%
“…Few studies have focused on this topic. However, across PTSD treatment studies the following developments have been found in some degree: worsening of psychiatric symptoms among some individuals that is not generally indicative of poorer long-term outcomes (Foa et al, 2002;Tarrier et al, 1999 ); and individual differences leading to variations in treatment response (Hembree et al, 2004;Morrisey et.al., 2005 ;Speckens et al, 2006 ;Tarrier et al, 1999 ). These developments make clear that further investigation is needed.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Foa and her colleagues (Foa, et al, 2002) found that greater numbers of women in a prolonged exposure condition experienced increased symptoms of anxiety and depression following imaginal exposure than did women in an imaginal exposure plus cognitive restructuring condition. However, short term increases in symptoms did not lead to worse PTSD symptoms at the conclusion of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…While the Emotional Experiencing Scale may be measuring an important factor contributing to psychotherapeutic change, it measures a distinct change process (Greenberg, Warwar, & Malcolm, 2008), therefore a more complete understanding of emotion processing could be provided by examining other related constructs. Affect experiencing has been found to be a significant predictor of psychotherapeutic change for processing trauma (Foa, Zoellner, Feeny, Hembree, & Alvarez-Conrad, 2002), resolving unfinished business (Greenberg & Malcolm, 2002) and discriminating successful psychotherapy outcomes according to reduced healthcare costs and improved functional status (Town, Abbass, & Bernier, 2013). Affect experiencing and depth of emotional experience are overlapping constructs (Warwar, 2003) but the latter focuses on verbal expression and does not include arousal of bodily affects in its conceptualization.…”
mentioning
confidence: 99%